Peran Lingkungan Terhadap Rasa Percaya Diri Mahasiswa Yang Mengalami Body Shaming - Haryati, Asti; Noviyanti, Annisa; Cahyani, Riza; Lesta, Lesta (Kuras Institute, 2021)
This study aims to see how the role of the environment on the self-confidence of students who experience body shaming, with a focus on students who experience body shaming treatment at IAIN Bengkulu. be a case of discussion, namely the role of the environment to foster self-confidence of students who get body shaming treatment. With a positive environment so that it can provide motivation and understanding to students who are victims of body shaming such as the support from a positive friendship environment so that it can provide understanding to students who experience body shaming to keep thinking positively and accepting themselves and being confident.